Calle 54 - Trueba, Fernando 1955.; Miramax (Burbank, California Miramax Home Entertainment, 2001)
A musical journey that captures the heart and soul of an entire culture. The sound that pulsates in hot backstreet clubs and recording studios. From Miami to Havana, the Bronx to Andalusia. A series of performances that reveal how these great Latin heroes use their extraordinary musical talent as a vehicle for storytelling, protest, sexuality and, above all, the celebration of life.
Associate producers, Rosa Bosch-Tequilagang and Fandango with the collaboration of Canal+France.
Cristina Huete, Fabienne Servan Schreiber.
Musicians: Eliane Elias, Michel Camilo, Chucho Valdés.
VHS format ; Dolby Surround.
In Spanish with yellow English subtitles.
Keywords: Jazz musicians; Latin jazz; Musical films